Analisis Perlindungan Hukum Terhadap Perawat Dalam Melakukan Tindakan Medis Pada Pelayanan Kesehatan Di Puskesmas - Ratna Kamilah; Supriadi Supriadi; Bona Parlidungan; Melda Amelia; Andri Herman Amelia (Journal of Innovative and Creativity, 2025)
Legal protection constitutes the protection of dignity and recognition of human rights possessed by legal subjects in accordance with legal provisions. Health represents one of the most important factors supporting human life in order to achieve a happy and prosperous existence. Health is also recognized as one of the fundamental human rights as stipulated in Article 28H paragraph (1) of the Constitution of the Republic of Indonesia of 1945, which states that every person has the right to obtain health services. In Law No. 17 of 2023 Concerning Health, health is defined as a state of physical, mental, and social well-being that enables every person to live productively in both social and economic terms. In order to realize such health, the Government must undertake efforts that can guarantee equitable access to health services for all segments of society in a structured and planned manner. The implementation of health improvement efforts can only be carried out by healthcare professionals, whether physicians or nurses, who possess the requisite competence and authority, which constitute one of the determining factors for public health services alongside behavioral, hereditary, and environmental factors. This research employs a normative juridical legal research methodology utilizing a descriptive-analytical approach to examine legislation (statutory approach) and conceptual approach. The findings of this research demonstrate that in providing health services to the community at primary health centers (puskesmas), legal protection for nurses in delivering health services is necessary, as established under the Regulation of the Minister of Health No. 26 of 2019 Concerning the Implementation Regulations of Law No. 38 of 2014 Concerning Nursing.